WhiskSight: A Reconfigurable, Vision-Based, Optical Whisker Sensing Array for Simultaneous Contact, Airflow, and Inertia Stimulus Detection - Kent, Teresa A; Kim, Suhan; Kornilowicz, Gabriel; Yuan, Wenzhen; Hartmann, Mitra J. Z.; Bergbreiter, Sarah (IEEE robotics and automation letters, 2021)
The development of whisker-based sensing systems faces at least two important technical challenges: scaling up the number of whiskers to large arrays while retaining a simple interface; and detecting the wide variety of stimuli that biological whiskers can sense, including both direct touch (contact) and airflow. Here we present the design for a whisker array that leverages a camera to measure whisker rotations without a complex interface. Whiskers are magnetically attached to an elastomer "skin," ensuring that the system is both scalable and reconfigurable. Direct contact is measured from the relative motion between each whisker and the skin, while airflow and inertia can be inferred from the signal experienced by all whiskers in the array. Individual whiskers can resolve the direction of contact transverse to the whisker within {6.2}^{° } and whisker rotation magnitude to within {0.5}^{° } . An algorithm is developed to distinguish inertial forces from airflow and contact.